Thermal Comfort Properties of Wool and Polyester/Wool Woven Fabrics Dyed in Black (Journal of Fiber Bioengineering and Informatics, 2013)
An abaya is a traditional Muslim woman's outer garment. It is black and worn on a day-to-day basis whenwomen are outside their homes. The abaya absorbs most of the heat from sunlight in a hot climate as itis black, making the wearer very uncomfortable. In order to reduce absorption of heat in an abaya andto make the wearer more comfortable, it is proposed that a treatment with a solar energy reflector couldenable the wearer to perspire less; thus allowing them to feel cooler. This paper investigates the thermalcomfort properties of plain-woven fabrics dyed in black and treated chemically to reflect a proportion ofsunlight's energy. The fabrics were made from 100% wool and two polyester/wool blends. The testingresults showed that the fabrics that had received the reflective treatment possessed marginally improvedthermal comfort properties as compared to fabrics without the treatment.